Malignant pleural effusion of renal adenocarcinoma - Mendez-Mathey, Vanessa E. (2018)
The malignant pleural effusion is a frequent complication of the cancer, is diagnosed by means of the finding cell neoplasicas in the pleural liquid or a cytology of positive pleura for malignant, can be present in 15 % of patients with diseases neoplasicas; the difficulty in breathing, cough or thoracic pain are the most frequent symptoms. The carcinoma of renal cells (CRC) or adenocarcinoma renal it represents approximately 2-3% of the neoplasias of the adult with an approximate incident of 5/100 000 persons, appears between 50 and 70 years, most of the times being characterized by the lack of clinical manifestations, since consequence of it the majority of the cases are diagnosed as advanced disease. The pleural metastasis is comparatively rarer than the pulmonary metastasis. We report the case of male patient with pleural malignant spillage of adenocarcinoma renal.